2011
DOI: 10.1111/j.1747-5457.2011.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass Balance Calculations for Different Models of Hydrocarbon Migration in the Jeanne d'ARC Basin, Offshore Newfoundland

Abstract: Basin and petroleum systems modelling is a powerful tool in petroleum exploration, but uncertainties remain in terms of the evaluation of a petroleum accumulation's size and quality, even when the petroleum system is well known and the latest modelling technology is applied. In order to interpret the results of a modelling exercise, it is necessary to understand the advantages and disadvantages of the various possible approaches used to assess petroleum migration and accumulation. This paper attempts to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The high expulsion efficiencies derived from the experimental data may be accentuated by the short migration distances due to samples size and flow rates due to higher experimental temperature compared to nature. Several field and basin modelling studies have reported similar expulsion efficiencies for liptinite-rich source rocks (see also Cooles et al, 1986;Littke et al, 1988;Leythaeuser et al, 1988;Rullkötter et al, 1988;Baur et al, 2011).…”
Section: S2mentioning
confidence: 65%
See 1 more Smart Citation
“…The high expulsion efficiencies derived from the experimental data may be accentuated by the short migration distances due to samples size and flow rates due to higher experimental temperature compared to nature. Several field and basin modelling studies have reported similar expulsion efficiencies for liptinite-rich source rocks (see also Cooles et al, 1986;Littke et al, 1988;Leythaeuser et al, 1988;Rullkötter et al, 1988;Baur et al, 2011).…”
Section: S2mentioning
confidence: 65%
“…Measurements from field and laboratory data suggest that finegrained rocks have low permeability coefficients ranging from 10 À18 to 10 À24 m 2 (Jones, 1981;Sandvik and Mercer, 1990;Deming, 1994;Nygard et al, 2004). Porosity and its evolution with burial are commonly correlated to intergranular permeability in numerical basin models (Aplin and Vasseur, 1998;Nygard et al, 2004;Baur et al, 2011). Porosity in fine-grained rocks shows tremendous variations with depth as evidenced by data collated by Yalcin et al (1997).…”
Section: Introductionmentioning
confidence: 84%
“…To assess the burial/thermal histories of the potential source rock, we used 1D Basin Modeling software (PetroMod), developed by the Schlumberger Information Solutions (SIS). Basin modelling has been successfully applied to some important petroliferous basins in world, such as the Masila Basin in Yemen by Hakimi et al (2010b), Shoushan Basin in Egypt by Shalaby et al (2011), the Jeanne D'Arc Basin, offshore Newfoundland by Baur et al (2011).…”
Section: Hydrocarbon Generation and Expulsionmentioning
confidence: 99%
“…These diagrams were adapted to perform numerical modeling of burial, erosion, and thermal histories in sedimentary basins, e.g., [33,30,34,35]. This method has become an important tool and successfully applied to search for new petroleum plays or for the evaluation of exploitable oil and gas accumulations around the world (e.g., [31,36,37]). In this chapter, quantitative one-dimensional basin modeling is performed for evaluating the thermal histories and timing of hydrocarbon generation and expulsion of the Nayfa, Madbi, and Shuqra source rocks in the Sayun-Masilah basin.…”
Section: Basin Modeling Proceduresmentioning
confidence: 99%